The significance of triumphing in adolescence: the perspective of the parent-child relationship - Pozdnyakova T.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to explore the correlation between achievement and well-being in boys and girls, as well as their parents. Methods and structure of the study. 146 people (university students and their parents) took part in the research. The main diagnostic tool was the TS 36 method (value orientations – 36 positions). In addition, the Parable test, the KOSKOM method (Communicative and social competence), the Self-Assessment test (author of the methods V.N. Kunitsyna), and the 16-factor questionnaire by R. Cattell were used. Results and conclusions. It has been established that success is highly valued by young people and their parents, with children having a higher level of importance. Interestingly, they value their own health even more than success in their chosen field. Health is of great importance for both children and parents, but for children, the importance of self-care, including attention to their health, appearance, interests, and status, is particularly relevant. For parents, there is a clear connection between health and caring for it, whereas some young people appreciate health but attach great importance to preserving, strengthening, and improving it, while others are indifferent to healthy lifestyles. The significance of success among children and parents does not have a statistically significant relationship with healthy lifestyles.. In a family, parents and children have different approaches to balancing the importance of achieving success with taking care of their health. They also have a direct connection to the value of good health.